2015
DOI: 10.1080/13825585.2015.1099607
|View full text |Cite
|
Sign up to set email alerts
|

When does prior knowledge disproportionately benefit older adults’ memory?

Abstract: Material consistent with knowledge/experience is generally more memorable than material inconsistent with knowledge/experience – an effect that can be more extreme in older adults. Four experiments investigated knowledge effects on memory with young and older adults. Memory for familiar and unfamiliar proverbs (Experiment 1) and for common and uncommon scenes (Experiment 2) showed similar knowledge effects across age groups. Memory for person-consistent and person-neutral actions (Experiment 3) showed a greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 66 publications
2
31
1
Order By: Relevance
“…It is a question for future research to understand the possible interplay of biases here. Overall, this finding fits with a broad body of research demonstrating the supportive nature of older adults' knowledge on their memory performance (e.g., Badham, Hay, Foxon, Kaur, & Maylor, 2015;Castel, 2005;Hess, 1990Hess, , 2005Hess et al, 1989;Hess & Tate, 1992;Laurence, 1967aLaurence, , 1967bMatzen & Benjamin, 2013;Sitzman et al, 2015), but adds to it with evidence that the stability of access to their knowledge may be critical in older adults' application of what they know.…”
Section: Discussionsupporting
confidence: 79%
“…It is a question for future research to understand the possible interplay of biases here. Overall, this finding fits with a broad body of research demonstrating the supportive nature of older adults' knowledge on their memory performance (e.g., Badham, Hay, Foxon, Kaur, & Maylor, 2015;Castel, 2005;Hess, 1990Hess, , 2005Hess et al, 1989;Hess & Tate, 1992;Laurence, 1967aLaurence, , 1967bMatzen & Benjamin, 2013;Sitzman et al, 2015), but adds to it with evidence that the stability of access to their knowledge may be critical in older adults' application of what they know.…”
Section: Discussionsupporting
confidence: 79%
“…Although much research indicates that the influence of prior experience is greater for older adults (see Umanath & Marsh, 2014, for a review), particularly for associative memory (e.g., Naveh-Benjamin et al, 2003), it might not always be the case. In recent work from our laboratory, we identified boundary conditions on this effect (Badham et al, 2016): Our data and review of the literature showed that there are many circumstances under which young and older adults make similar use of pre-experimental knowledge and the same is true of the current word frequency data. In Badham et al (2016), age deficits in associative memory were reduced by using semantically related word pairs (e.g., spear-pistol, horn-trombone) compared to unrelated word pairs (e.g., whiskey-jacket, hawk-volcano) but only if the relations were unique to each pair.…”
Section: Discussionmentioning
confidence: 92%
“…This has been shown across a variety of paradigms, largely in the domain of associative memoryfor example, memory for plausible compared to implausible grocery prices (Castel, 2005), memory for typical compared to atypical actions in scripts (Hess, 1985), and memory for associations between semantically related compared to unrelated words (Badham, Estes, & Maylor, 2012). However, recent research from our laboratory (Badham, Hay, Foxon, Kaur, & Maylor, 2016;Badham & Maylor, 2015) and others (Mohanty, Naveh-Benjamin, & Ratneshwar, 2016) has shown that prior knowledge does not alleviate age-related memory deficits under certain conditions. This poses a challenge to existing theory which is explored further in the current article through examination of age differences in established memory paradigms that are known to be influenced by word frequency.…”
mentioning
confidence: 99%
“…Studies in which participants are required to generate scripts for routine events show that older and younger adults generate similar numbers of script items (Light & Anderson, 1983), and the script content is similar (Rosen, Caplan, Sheesley, Rodriguez, & Grafman, 2003), which suggests that access to generic event information is maintained in older age. Moreover, while both older and younger adults show a mnemonic benefit for material that is schemaconsistent, under some circumstances this effect may be greater for older adults (Badham, Hay, Foxon, Kaur, & Maylor, 2016;Umanath & Marsh, 2014). On the other hand, repeated experiences of similar events can make retrieval of specific instances more difficult (Farrar & Goodman, 1992;Willén, Granhag, & Strömwall, 2016).…”
Section: Autobiographical Memory In Ageingmentioning
confidence: 99%